THE POLICY OF ARABIC CAMP PROGRAM IN ASY - SYARIFAH ISLAMIC SENIOR HIGH SCHOOL (MAQBA) (ARABIC LANGUAGE POLICY STUDIES) - Busri, Hasan; Munir, Muhamad Misbahul (Cordova Journal language and culture studies, 2023)
Asy - Syarifah Islamic Senior High School or it’s called MAQBA (school of learning language and Quran) is one of the language school In Mranggen district Demak regency. This school is a boarding school system that has two special programs, those are language and Quran. Asy - Syarifah Islamic Senior High School exists in 2007 but in 2017 it has already had language program and launched it in 2017 by creating launching language day. From that agenda, the school has some rules of language day and some supported programs that support the language program in Asy - Syarifah Islamic Senior High School or MAQBA During this time, the Arabic learning program doesn’t give the students a good improvement in it yet. There are some problems while running this program. Those are many students don’t graduated from the Islamic junior high school and also we still need many qualified teacher that has an ability to help this Arabic learning program running well. Beside that, the Islamic boarding school still doesn’t give support yet according to this program, because the functionaries of Islamic boarding school still feel confused to get the way to have skill in a short time. Because of that, MAQBA has a concept of learning Arabic language by Arabic Camp Program as a medium for students and teachers to learn and practice Arabic in International atmosphere through fun learning and non-formal education method, where the Arabic camp program will run in the beginning of the academic year. And this program aim at the students and also all of the teachers that can help the programs later if the Arabic camp program has finished. MAQBA Asy-Syarifah needs to take a policy by initiating an intensive, comprehensive and fun Arabic language learning system to produce students who have qualified Arabic language competences. This is the aim of this research. This research uses descriptive qualitative research methods. The results of this study indicate that MAQBA Asy-Syarifah is serious about guarding the development of Arabic language competencies by issuing a policy of holding an Arabic Camp Program for new students of MAQBA Asy-Syarifah. This seriousness is shown by preparing the best designed study time and curriculum, and also cooperate with another institution from Pare Kediri to have an Arabic Camp System by Pare System in developing a language especially for Arabic.